Financial inclusion, remittances and household consumption in sub-Saharan Africa: Evidence from the application of an endogenous threshold dynamic panel model - Ahmat-Tidjani Mahamat Ibrahim (Economics and Business Review)
This paper examines the effect of financial inclusion on per capita household consumption expenditures in sub-Saharan Africa. It uses data from 28 countries over the period 2004–2022 and an endogenous threshold dynamic panel model for econometric estimations. The study finds evidence of the asymmetric effects of financial inclusion on household consumption expenditures in the region. There exists a remittances threshold that varies between 2.6% and 6.5% of an average sub-Saharan African country’s GDP below which financial inclusion increases per capita household consumption expenditures. However, above that threshold, financial inclusion does not contribute to improving household welfare in the region. Therefore, given that the effect of financial inclusion increases with liquidity constraints, policies that target a better allocation of remittances received would amplify the effect of financial inclusion on household consumption.